“It’s easier talking to a machine”: Privacy, motivation, and the underuse of English language labs in a Sino-foreign university in China - Duffy, Liam; Binghang, Lin (Journal of International Students, 2026)
Despite significant investment, English language labs (ELLs) at transnational campuses remain underutilized beyond mandatory course requirements. This qualitative case study draws on thematic analysis of interviews with 22 Chinese undergraduates at a Sino-American branch campus in mainland China. Students value the ELL’s diagnostic feedback and low-anxiety speaking practice. However, voluntary use is hindered by severe privacy concerns and accent-related anxiety in open layouts, widespread unawareness, outdated and generic content, and competition from mobile apps. Three learner personas emerge: the Anxious Beginner, Test-Prepper, and Advanced Critic. Informed by self-determination theory and foreign language anxiety research, the findings highlight how cultural “face” concerns and poor facility design undermine engagement. Students propose soundproof booths, targeted promotion, and personalized diagnostic pathways. The study offers actionable recommendations to transform ELLs into inclusive, sought-after resources in English-medium transnational education.